Work Flexibility and Rewards Affect Gen Z Employee Retention Through Job Satisfaction Mediation - Lazuardi, Muhammad Abdul Latief; Hasanudin; Yakin, Ikram (MultiTech Publisher, 2025)
The phenomenon of job hopping is increasingly common among Generation Z, who seek flexible work arrangements, fair rewards, and job satisfaction. In Indonesia, particularly in West Kalimantan, Gen Z dominates the productive-age population, prompting companies to adopt effective retention strategies. This study investigates the effect of work flexibility and rewards on employee retention, with job satisfaction as a mediating variable. The research involved 250 Gen Z employees working in the creative industry companies in West Kalimantan. Respondents were aged 17–28 and had at least six months of work experience, working in hybrid arrangements. Data was collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. Results show that both work flexibility and rewards significantly influence employee retention directly and indirectly through job satisfaction. These findings highlight that Gen Z values a supportive, flexible work environment and transparent reward systems. Enhancing job satisfaction is essential for increasing their retention in organizations